Alterations in event-related potential responses to empathy for pain in schizophrenia. (30th July 2016) - Gonzalez-Liencres, Cristina; Brown, Elliot C.; Tas, Cumhur; Breidenstein, Anja; Brüne, Martin
Abstract: Lack of empathy is a critical factor impacting on social functioning and quality of life in schizophrenia. There is, however, a paucity of research into the underlying neurophysiological correlates of empathy deficits in this disorder. Accordingly, we sought: (1) to identify whether dysfunctional empathic abilities in schizophrenia are related to alterations in early or late brain processes, and (2) to explore the potential relationship between brain activity and mood, self-reported empathy and symptom severity. Eighteen patients with schizophrenia and 21 healthy matched controls performed an empathy-for-pain paradigm where photographs of hands in neutral or painful situations were shown while we recorded their electroencephalography (EEG), and we examined mood, empathic concern for others and symptom severity. Significant group differences between patients and controls emerged in early (50–150 ms after stimulus onset) and late (after 300 ms) timeframes. Moreover, brain activity was related with unpleasantness ratings in all participants, with self-reported empathic concern only in controls and with negative mood and personal distress only in patients. Differences in social behavior in schizophrenia may be explained by early as well as late differences, affecting mostly the early frontocentral ERPs, i.e. those suggested to correspond to the emotional sharing component of empathy. Highlights: We examined early and late ERPs in people with schizophrenia and healthy controls. We recorded EEG while patients and controls performed an empathy task. Patients with schizophrenia present empathy deficits. These deficits may be explained by differences in early and late neural processes. ERPs induced by empathic stimuli correlated with empathy and mood scores.